Frustrated Lewis Pairs I : uncovering and understanding - Stephan, Douglas W. (Topics in current chemistry, 2013)
Discovery of Frustrated Lewis Pairs: Intermolecular FLPs for Activation of Small Molecules, by Douglas W. Stephan Intramolecular Frustrated Lewis Pairs: Formation and Chemical Features, by Gerald Kehr, Sina Schwendemann, Gerhard Erker Frustrated Lewis Pair Mediated Hydrogenations, by Douglas W. Stephan, Gerhard Erker Amine-Borane Mediated Metal-Free Hydrogen Activation and Catalytic Hydrogenation, by Victor Sumerin, Konstantin Chernichenko, Felix Schulz, Markku Leskelä, Bernhard Rieger, Timo Repo Hydrogen Activation by Frustrated Lewis Pairs: Insights from Computational Studies, by Tibor András Rokob, Imre Pápai Quantum Chemistry of FLPs and Their Activation of Small Molecules: Methodological Aspects, by Birgitta Schirmer, Stefan Grimme Computational Design of Metal-Free Molecules for Activation of Small Molecules, Hydrogenation, and Hydroamination, by Zhi-Xiang Wang, Lili Zhao, Gang Lu, Haixia Li, Fang Huang Computational Studies of Lewis Acidity and Basicity in Frustrated Lewis Pairs, by Thomas M. Gilbert Solid-State NMR as a Spectroscopic Tool for Characterizing Phosphane - Borane Frustrated Lewis Pairs, by Thomas Wiegand, Hellmut Eckert, Stefan Grimme